Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/igc.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Adenosquamous Carcinoma Compared With Adenocarcinoma in Uterine Cervical Cancer: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: This meta-analysis suggests that ASC may have poorer outcomes compared with AC of the cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 30 publications
(13 reference statements)
4
19
0
Order By: Relevance
“…A Korean multicenter retrospective study (total n ¼ 1323; AC/ASC, n ¼ 255) reported that AC histology was associated with poor survival outcomes than SCC, and prognosis of ASC histology was closer to that of SCC histology [23]. Conversely, a meta-analysis reported that ASC may have poorer outcomes compared with AC of the cervix [24]. Our study demonstrated that ASC seemed slightly worse than AC in univariate analysis, but they were not significantly different on RFS and CSS in multivariate analyses (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 92%
“…A Korean multicenter retrospective study (total n ¼ 1323; AC/ASC, n ¼ 255) reported that AC histology was associated with poor survival outcomes than SCC, and prognosis of ASC histology was closer to that of SCC histology [23]. Conversely, a meta-analysis reported that ASC may have poorer outcomes compared with AC of the cervix [24]. Our study demonstrated that ASC seemed slightly worse than AC in univariate analysis, but they were not significantly different on RFS and CSS in multivariate analyses (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 92%
“…Patients in the later stages of cervical cancer with invasion or metastasis have a significantly worse prognosis (29). Fewer than 20% of women with stage IV cervical cancer survive for ≥5 years (30).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies reported poor survival for patients with ASC. Lee et al [16] demonstrated that ASC may have poorer outcomes compared with AC of the cervix in meta-analysis. Farley et al [17] observed an increased risk of death among patients with ASC histology, compared to those with AC histology.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that ASC histology is associated with a worse prognosis, compared to that of AC histology [16,17],other studies found that early-stage AC and ASC are more aggressive and have worse prognoses, compared to SCC [6,[18][19][20][21]. Given that only a few studies have directly compared outcomes between patients with AC and those with ASC [8,17], the relationship between histology findings (AC or ASC) and the outcome of cervical cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%